If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 88 + -26 = 10(h + -6) Combine like terms: 88 + -26 = 62 62 = 10(h + -6) Reorder the terms: 62 = 10(-6 + h) 62 = (-6 * 10 + h * 10) 62 = (-60 + 10h) Solving 62 = -60 + 10h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-10h' to each side of the equation. 62 + -10h = -60 + 10h + -10h Combine like terms: 10h + -10h = 0 62 + -10h = -60 + 0 62 + -10h = -60 Add '-62' to each side of the equation. 62 + -62 + -10h = -60 + -62 Combine like terms: 62 + -62 = 0 0 + -10h = -60 + -62 -10h = -60 + -62 Combine like terms: -60 + -62 = -122 -10h = -122 Divide each side by '-10'. h = 12.2 Simplifying h = 12.2
| p-26=10(20-6) | | -38-4(15)= | | 7x-34=5y | | p-26=10(18-6) | | -38-4(12)= | | -38-4(6)= | | -a+4a= | | 18+9(x)=288 | | 18+9(24)= | | x^4-9*x^3+27*x^2-91*x=0 | | 45+18= | | -3x-5=-35 | | 4a-a=23 | | x-3y+2z=-28 | | 2(x+3)=14-x | | 5(x-3)=2(4x+1) | | 3(12-x)-6=2 | | -v+3=4 | | 3x+3y+z=-11 | | 32+4(x)=180 | | 224=-8m | | 39+3(x)=174 | | 5m-2(m+2)=-(2m+14) | | 88-18=9(h-5) | | 4a+2ac+6ab=0 | | p-18=9(20-5) | | 0.25(16x-8)+6=12-5x | | 13x+9+5x+9=180 | | p+0.15p=29.5 | | p-18=9(18-5) | | Log[5]72-Log[5]x=3Log[5]2 | | 4xy-x^2+5x=0 |